The construction of iap methodology: an exploration into the author’s work (2009)
This article is circumscribed to a ten-year period, on the hypothesis according to which between 1967, with the publication of the book “La subversión en Colombia”, and 1977, with the event named “Simposio Mundial de Cartagena sobre Investigación Activa”, Orlando Fals Borda formulated the basis of which, from the early eighties, is known as “Metodología de la Investigación Acción Participativa, IAP”. We will not examine step by step the insertion of the author in the sociopolitical national context and the possible changes, leaps and ruptures in the level of his thought for two reasons: First, because this does not happen as a very cause-effect relationship and, second, because the temporality of these processes is not purely historic, given that they deliberate also occur in the individual’s unconscious. We will be limited to indicate only some events that could have been crucial in the formulation of his API methodology.